Use Of E-Learning To The Effectiveness Of Students In Coronavirus Pandemic - Fachroh Fiddin; Bustami Bustami (EDUTEC : Journal of Education And Technology, 2021)
Abstract. This research aims to determine the effectiveness of student learning in the coastal areas of the island of Sumatra at the time of the Covid-19 virus pandemic using e-learning. The respondent is an accounting student at the state Polytechnic in Bengkalis where almost all students live in the coastal areas of the island and differ from those in urban areas. The variables examined the perception of benefits, perception of ease, and quality of service towards the use of e-learning and the effectiveness of student learning. The results showed a perception of benefits and quality of service impacting the use of e-learning and the effectiveness of student learning. While the perception of simplicity does not affect the use of e-learning and the effectiveness of student learning. The results of research using track analysis show that variable perception of benefits and quality of service affects the effectiveness of learning through the use of e-learning as a mediation variable. While the variable perception of ease has no influence on the effectiveness of student learning through the use of e-learning as a mediation variable.